Removal of Hg from Real Polluted Sediments Using Enhanced-EK Decontamination: Verification of Experimental Methods and Batch-Test Preliminary Results - Danilo Malarbì; Pietro P. Falciglia; Federico G. A. Vagliasindi (Journal of Chemistry)
The aim of the research is to apply a biosurfactant-enhanced-EK technology to marine sediment contaminated by high level of Hg. In this work, data from batch-tests using different novel biosurfactant agents were reported. In addition, a dedicated EK bench-scale apparatus was designed and carried out. Technical test was also performed to evaluate the optimal operating features of the EK bench-scale apparatus, assessing the influence of applied voltage and treatment time on the current intensity and electroosmotic flow. Batch experiments were conducted using two sugar esters as biosurfactants and EDTA salt at different concentrations. Results showed that the maximum extraction efficiency was observed for the biosurfactant Olimpicon GC (15%), for which the Hg extraction was shown to be 3.6-fold higher than for 0.2 M EDTA. From technical tests, the observed reduction of current intensity and electroosmotic flow with time highlights the necessity of using conditioning agents during the treatment. Data demonstrates also the good working features of the experimental apparatus. Preliminary results show that EK treatment jointly with biosurfactants such as sugar esters could be a better choice for the remediation of Hg-polluted sediments. The results obtained are of scientific and practical interest and can be used for further researches.